Mediation of Intellectual Capital in the Relationship of Industry Experience, Marketing Capability and Market Research on Strategy Creation and Value Added in the Coffee Industry in Indonesia - Permana, Dudi (The Eastasouth Management and Business, 2024)
In the Indonesian coffee business, this study examines the role that intellectual capital plays as a mediator between industry experience, marketing capability, market research, strategy design, and value-added outcomes. A structured survey is used to gather data from 228 stakeholders in the coffee business using a quantitative technique. Analysis using structural equation modeling (SEM) is done to look at the connections between the research variables. The results show that market research, marketing expertise, and industry experience all significantly improve strategy development and value-added results. Furthermore, intellectual capital plays a semi-mediating function in these connections, emphasizing its ability to convert market insights, industry expertise, and marketing initiatives into strategic outcomes and value generation. These results advance our knowledge of the dynamics at play in the coffee business and provide useful information to stakeholders looking to improve their competitive status and promote long-term expansion.